2022
DOI: 10.1021/acsomega.1c05838
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Isotope Fractionation in U3O8 during Thermal Processing in Humid Atmospheres

Abstract: The incorporation of oxygen isotopes from water into uranium oxides during industrial processing presents a pathway for determining a material's geographical origin. This study is founded on the hypothesis that oxygen isotopes from atmospheric water vapor will exchange with isotopes of oxygen in solid uranium oxides during thermal processing or calcination. Using a commonly encountered oxide, U 3 O 8 , the exchange kinetics and equilibrium fractionation with water vapor (in a concentration range of 50−55% rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Thus, we attribute the first-order transition state, at 300–400 °C, to the fact that the δ 18 O values reach a minimum and the second-order transition state, at 500–600 °C, to the inverse trend of the oxygen isotopic composition. We consider the possible isotope exchange with humidity H 2 O at 400 °C (Klosterman et al 22 ) minor to the isotope effect of the observed phase transition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, we attribute the first-order transition state, at 300–400 °C, to the fact that the δ 18 O values reach a minimum and the second-order transition state, at 500–600 °C, to the inverse trend of the oxygen isotopic composition. We consider the possible isotope exchange with humidity H 2 O at 400 °C (Klosterman et al 22 ) minor to the isotope effect of the observed phase transition.…”
Section: Discussionmentioning
confidence: 99%
“…Klosterman et al 16 synthesized U 3 O 8 from uranium peroxide at 300−1000 °C and reported a fractionation of about −22‰ up to about −5‰, respectively, between the oxide and atmospheric oxygen with a retrograde isotope effect. Klosterman et al 22 determined the fractionation of oxygen isotopes between U 3 O 8 and N 2 /O 2 atmosphere at 400, 600, and 800 °C, and different calcination times (between 1 and 72 h) reported an average of Δ 18 showed that the cooling profile at the end of the fabrication process of U 3 O 8 determines the final oxygen isotopic composition, yielding a significant isotope effect in the order of 30‰, and that the interaction with atmospheric oxygen is the primary process that controls the δ 18 O value of U 3 O 8 . The common conclusion of the above studies is that the reaction with atmospheric oxygen is a crucial factor in determining the final oxygen isotopic composition of U 3 O 8 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 The comparison of several oxygen extraction methods from UO 2 , U 3 O 8 , and UO 3 compounds has revealed that different amounts of water molecules present in the uranium oxides must be removed, as they interfere with the isotope measurement 11 and exchange reactions with humid atmospheres, affecting the oxygen fractionation. 15 Klosterman et al 15 synthesized U 3 O 8 from uranium peroxide at 300−1000 °C, reporting fractionation of about −22‰ up to about −5‰, respectively, between the oxide and atmospheric oxygen with a retrograde isotope effect. 16 The exposure of U 3 O 8 and UO 2 to humidity in an oxidizing atmosphere showed that hydrated uranium oxide grows as a secondary mineral (metaschoepite) on aged U 3 O 8 and UO 2.…”
Section: Introductionmentioning
confidence: 99%